Impact of Charge on Strange Compact Stars in Rastall Theory - Malick Sallah; Muhammad Sharif (Universe)
Within the framework of Rastall theory, we investigate the impact of charge on the structural development of different types of spherically symmetric anisotropic stars. To do so, we present modified field equations based upon the Finch–Skea metric potentials expressed in terms of three parameters <semantics>(A,B,C)</semantics>. These constants are determined using suitable matching conditions and observational data for compact objects which include Her X-1, SAX J 1808.4-3658, PSR J038-0842, LMC X-4 and SMC X-1. The equation of state offered by the <semantics>MIT</semantics> bag model for quark–gluon plasma is used to investigate the inner structure and other characteristics of these compact objects. For a fixed bag constant, <semantics>B=60<mspace width="3.33333pt"></mspace>MeV/fm3</semantics>, and two sets of the Rastall and charge parameters, <semantics>ζ=0.255,0.259</semantics> and <semantics><mover accent="true">Q˜</mover>=0.2,0.7</semantics>, respectively, we analyze the consistency of the matter variables in the model and other physical parameters such as energy conditions, stellar mass, compactness, and surface redshift. In addition, we assess the stability of the constructed model through two different approaches. It is found that the obtained model is physically viable and stable.